PENGARUH PENERAPAN KINERJA LINGKUNGAN, PENGUNGKAP LINGKUNGAN, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Ary Meizary; Firmansyah Yunialfi Alfian (Bajang Institute, 2023)
This study aims to examine the effect of implementing environmental performance, environmental disclosure, sales growth and firm size on firm value. The research was conducted on Manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The data used in this study is secondary data in the form of annual financial reports and company sustainability reports for 2018-2020. Sampling by purposive sampling using 12 companies as data samples. Multiple linear regression test was used to see the effect of the independent variable on the dependent variable. The results of the analysis show that environmental performance and firm size have an effect on firm value. Meanwhile, Environmental Disclosure and Sales Growth have no effect on Company Value